2003
DOI: 10.1084/jem.20030351
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for OX40 in T Cell–mediated Immunopathology during Lung Viral Infection

Abstract: Respiratory infections are the third leading cause of death worldwide. Illness is caused by pathogen replication and disruption of airway homeostasis by excessive expansion of cell numbers. One strategy to prevent lung immune–mediated damage involves reducing the cellular burden. To date, antiinflammatory strategies have affected both antigen-specific and naive immune repertoires. Here we report a novel form of immune intervention that specifically targets recently activated T cells alone. OX40 (CD134) is abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 26 publications
8
110
2
Order By: Relevance
“…Furthermore, redundancy in such late costimulators that act at the same stage as OX40/OX40L (such as 4-1BB/4-1BBL) would provide the signals required for maintenance of sufficient inflammation and the development of immunological memory (32, 34, 39, 40). Interestingly, OX40 or OX40L blockade is actually beneficial in infectious diseases associated with immunopathology, such as virally induced myocarditis (41), respiratory viruses (34), and polymicrobial sepsis (42), which are significant complications of current treatment strategies for arthritis. For these reasons, blockade of late T-cell costimulators and their receptors should be tested in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, redundancy in such late costimulators that act at the same stage as OX40/OX40L (such as 4-1BB/4-1BBL) would provide the signals required for maintenance of sufficient inflammation and the development of immunological memory (32, 34, 39, 40). Interestingly, OX40 or OX40L blockade is actually beneficial in infectious diseases associated with immunopathology, such as virally induced myocarditis (41), respiratory viruses (34), and polymicrobial sepsis (42), which are significant complications of current treatment strategies for arthritis. For these reasons, blockade of late T-cell costimulators and their receptors should be tested in humans.…”
Section: Resultsmentioning
confidence: 99%
“…OX40 Ϫ/Ϫ CD8 cells showed a more pronounced defect in producing TNF compared with IFN-␥, indicating that the OX40 signal may differentially target this cytokine in fully activated CD8 T cells. Of note, a previous report showed that blocking OX40L with OX40-Ig reduced TNF production from CD8 T cells after influenza virus infection (55), and more recently Ito et al (56) showed that OX40 signaling selectively promoted TNF secretion in human CD4 T cells in vitro. Thus, the regulation of TNF synthesis by OX40 may be common to CD4 and CD8 T cells in various inflammatory circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known to what extent CD4 cells contribute to lung immunopathology after influenza infection, however, it is known that Th2 cells do not protect against lethal influenza infection [51] and the reason for this may be due to increased pathology mediated by the type 2 cytokines, IL-4 and IL-5 leading to eosinophilia. Recently, it has been shown that blocking the OX40-OX40L costimulatory pathway can lead to decreased T cell influx into the lungs and diminished immunopathology after influenza infection [54]. It remains to be determined if CD4 and CD8 cells contribute equally to immunopathology after infection with more virulent strains of influenza.…”
Section: Cd4 Effector Mechanisms and Protectionmentioning
confidence: 99%